La calidad del servicio educativo y de atención de los centros infantiles del Buen Vivir. Perspectiva y expectativa de los padres de familia. Estudio de caso en el CIBV La casa de mis Pequeños Traviesos, de la parroquia El Corazón, cantón Pángua, Provincia Cotopaxi - Pilatasig Gavilanes, Luis Victor (2015)
This research work was conducted in the CIBV "The house of my little naughty" belonging to the Heart parish, canton Pangua; this was done with the participation of teachers, parents and mothers of the institution and the community. It was necessary to analyze quality of education and care of children's centers for Good Living from the perspectives and expectations of parents; taking into account that early childhood is considered the primary stage in the life of human beings, where the development of skills and abilities is enhanced. For this we have taken into account the various development theories proposed by several authors who have presented their research, among the highlights are: Piaget, Vygotsky, Ausubel, Gardner and Montessori. Based on these studies, the development of early childhood is also addressed from the cultural, spiritual and ancestral rescuing community values. In this work emphasis was given to the influence of family and parental opinion about the quality of service and attention that children's centers provide good living to children of the community.